Water Source Signatures in the Spatial and Seasonal Isotope Variation of Chinese Tap Waters. Issue 11 (20th November 2018) - Wang, Shengjie; Zhang, Mingjun; Bowen, Gabriel J.; Liu, Xuemei; Du, Mingxia; Chen, Fenli; Qiu, Xue; Wang, Liwei; Che, Yanjun; Zhao, Guoyong
Abstract: Different water sources exploited for public use have different exposure to risks associated with climatic and environmental change. Isotope ratios of tap water have previously been studied as a potential tool to link public supply waters with water source characteristics at local to continental scales, providing information on the footprint of and potential risks associated with the water sources used. Work that combines intensive spatial and temporal sampling with independent water management data has been limited, however. In this study, an extensive observation network was established during 2014–2016 to provide monthly tap water sampling across China. We show that the spatial distribution of annual mean tap water isotope ratios is generally consistent with that of local precipitation across China. We identify seasonal correlation between tap water and precipitation isotope ratios in south China, where use of surface water is prevalent. In contrast, relatively invariant tap water isotope ratios elsewhere in China, which are not correlated with seasonal variation of precipitation isotope ratios, can be attributed to use of groundwater or water from river basins with longer storage times. The tap water isotope signatures identified here could be widely applied to characterize water supplies and associated sustainability challenges in different regions worldwide. Key Points: A new nationwide network of tap water isotope data across China was established Connection between monthly stable isotopes in tap water and precipitation is identified Diagnostic patterns of tap water isotopes are associated with water resource use